Kepribadian Tokoh Perempuan dalam Kumpulan Cerpen Cinta Tak Pernah Menari Karya Asma Nadia - Febriyan Darma Kartika (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to describe the personality of female characters contained in the short story collection Cinta Never Dance by Asma Nadia and describe the implications of the personality of female characters contained in the collection of short stories Cinta Never Dance by Asma Nadia in literature learning in high school. This type of research is qualitative research with descriptive methods. The data in this study is in the form of a series of sentences, words, character utterances, character actions, and author's narratives that describe the personality of female characters in the short story collection Cinta Never Dance by Asma Nadia. The data collection technique in this study is a documentation technique or literature study. The data validity technique in this study is the triangulation technique. Data is analyzed in three activity flows, namely data reduction, data presentation, and data verification. Based on the results of the study, it was concluded that 1) the short story entitled Telephone Pinky there were four female characters, namely Inne, Sita, Mama, and Mbak Wiwi. Inne has a melancholy personality, Sita has a plegmatic personality, mama has a sanguinis personality, and Mbak Wiwi has a sanguinis personality, 2) a short story entitled Jendela Rara there are three female characters, namely Rara, Emak, and Asih. Rara has a choleric personality, emak has a plegmatic personality, and Asih has a choleric personality, 3) a short story entitled Cinta yang Yang Indah there are two female characters, namely Indah and Mala. Indah has a sanguinis personality and Mala has a sanguinis personality, 4) Ten Million Rupiah short stories there are two female characters, namely Ibu and Sri. Mom has a melancholy personality and Sri has a plegmatic personality, 5) Jhoni the Boss's short story has one female character, namely Mrs. Jhoni. Jhoni's mother has a melancholy personality, 6) the short story Tears Bireuen there is one female character, namely Inong. Inong has a melancholy personality, 7) the short story Ibu Goes A Month there is one female character, namely Mrs. Saiman. Mrs. Saiman has a choleric personality, 8) short stories Loose Rasa there are four female characters, namely Widi, Mia, Uthe, and Sarah. Widi has a choleric personality, Mia has a plegmatic personality, Uthe has a sanguinis personality, and Sarah has a sanguinis personality, 9) Newspaper short stories there are two female characters, namely Wife Maman and Mbak Kinarsih (Wife of Japra). Maman's wife has a plegmatic personality and Mbak Kinarsih has a sanguinis personality, 10) a short story entitled Jejak Surga there are six female characters, namely Ken, Mama Alia, Bik Nah, Ibu Dedi, the woman who guards the rice stall, and Ayuningsih.Ken has a sanguinis personality, mama Alia has a choleric personality, Bik Nah has a plegmatic personality, Dedi's mother has a sanguinis personality, the rice stall keeper woman has a choleric personality,  and Ayuningsih has a personality and is plegmatic.